Аномальна поведінка кінетичних параметрів під час формування структури органо-неорганічних полімерних систем - Юрженко, М.В.; Мамуня, Є.П.; Буато, Ж.; Сетр, Ж.; Лебедєв, Є.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The dependences of physical characteristics during forming a structure of organic-inorganic systems (OIS) are investigated. The anomalous non-monotonic tendency of changing the physical parameters is found. This effect is explained by a complicated structure of OIS that consists of two interpenetrating hybrid organic-inorganic networks which are characterized by different rates of forming.